1983
DOI: 10.2466/pr0.1983.52.1.263
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Race Differences in Psychiatric Symptomatology in Phencyclidine Psychosis

Abstract: The medical records of 153 psychiatric admissions who were determined to be Phencyclidine toxic were analyzed for the presence of various categories of psychiatric symptoms. Aggression was observed during the hospital stay by 58% of the patients followed closely by bizarre behavior (55%) and anxiety (53%). 116 males did not differ from 37 females in observed symptoms but 112 blacks showed more bizarre behavior than 41 whites. Further analysis indicated that the black-white difference was due to the significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Among individuals seeking treatment for drug-induced problems with psychedelic substances, many report problems with anxiety symptoms (Abraham & Fava, 1999;Griffin, Garey, Daul, & Goethe, 1983;Nicholi, 1984;Smith & Seymour, 1994). For example, Yago et al (1981) found that approximately 50% of individuals presenting for drug-induced problems in an emergency room setting and meeting criteria for PCP use in the past 48 h reported significant elevations in anxiety symptoms.…”
mentioning
confidence: 96%
“…Among individuals seeking treatment for drug-induced problems with psychedelic substances, many report problems with anxiety symptoms (Abraham & Fava, 1999;Griffin, Garey, Daul, & Goethe, 1983;Nicholi, 1984;Smith & Seymour, 1994). For example, Yago et al (1981) found that approximately 50% of individuals presenting for drug-induced problems in an emergency room setting and meeting criteria for PCP use in the past 48 h reported significant elevations in anxiety symptoms.…”
mentioning
confidence: 96%